CRM PERFORMANCES ACCENTED WITH THE IMPLEMENTATION OF E-COMMERCE TECHNOLOGY - Isaković, Ines (Journal of Applied Engineering Science, 2013)
Anywhere you live, you must have heard for e-commerce in last few years, because there are a lot of e-mails with a many advertisements with e-commerce purchasing. Maybe, you do not know exactly what e-commerce means. In my country, for sure, there are many persons that do not even heard about that opportunity for our economy, which Internet established as a part of business innovation. Because of that this paper is talking about e-commerce and datebases in details, as well as how it affect on the Customer Relationship Management